Dynamics of Authority Distribution: Exploring Efforts to Re-Centralization Central Government Authority - Zanuar Nur Hidayat; Moh. Hariyanto; Wahyu Eko Bayu Saputro; Muhammad Zulfan Raghibie (Fakultas Hukum Universitas Lampung, 2025)
This article examines recentralization and its impact on power relations between the central and regional governments in Indonesia. The study employs a doctrinal legal research method using conceptual and statutory approaches with qualitative descriptive analysis. The findings show that recentralization occurs through various legal mechanisms, including the transfer of licensing authority from regional governments to the central government under the Job Creation Law, the imposition of development priorities through the National Strategic Program based on presidential authority, and the revocation of regional regulations by ministers deemed inconsistent with higher laws. These practices have produced asymmetrical and subordinative power relations, significantly reducing regional autonomy. Overall, recentralization threatens regional interests and undermines the principles of decentralization established during the reform era..